Design and instrumentation of a coronary care unit - Kireçyan, Ari. (Thesis (M.S.) - Bogazici University. Institute of Biomedical Engineering, 1985., 1985)
In this study, the main principles that must be obeyed in the design and equipment selection of a coronary care unit are investigated along with the architectural steps which could be used in the establishment of such a unit. Information is given about the bedside monitors, central console monitors and other assisting devices which must be present in an optimal coronary care unit (CCU). The operation principles of these devices are explained by means of block diagrams. The computerized forms of these units which are widespread in developed countries and their advantages are also explained. The characteristics that the hospital's electrical network must have in order for the desired CCU to be realized and the precautions to ensure patient, user and visitor safety are described. The coronary care unit in the Etfal Hospital, the Cerrahpasa, a Hospital, the Haydarpaşa Gogus Cerrahisi Hospital and in the Medical University of Istanbul Çapa Hospital which are functioning in Istanbul are investigated. Information is given about the existing design and some suggestions to solve the problems that arise are offered. In short, the major purpose of this thesis is to built up a source of information on how to realize a CCU design at optimal usefullness and efficiency, taking the economy and technical conditions of the country into consideration.
Keywords: Coronary care units.